PHENOL CONTENT, ANTIOXIDANT ACTIVITY AND FIBERS PROFILE OF FOUR TROPICAL SEAGRASSES FROM INDONESIA - Joko Santoso; Siti Anwariyah; Ria Octavia Rumiantin; Aristi Pramadita Putri; Nabila Ukhty; Yumiko Yoshie- Stark (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Extracts of methanol, ethyl acetate, and n-hexane of four species of Indonesian seagrasses were used to determine the total phenol contents and their antioxidant activities.  Total phenol contents of each extract was determined by spectrophotometer using Follin-Ciocalteu reagent, and the antioxidant activity was measured using 1,1-diphenyl-2-picrylhydrazyl (DPPH).  The profile of fibers of each fresh seagrass was performed according to an enzymatic-gravimetric method. All of methanol extracts contained high number of total phenol, except Syringodium isoetifolium the highest content was found in ethyl acetate extract; so that methanol extracts of Thalassia hemprichii, Cymodocea rotundata, Enhalus acoroides and ethyl acetate extract of Syringodium isoetifolium had the highest activities on scavenging DPPH radical.  The phenol content in tropical seagrasses was tending to soluble in polar and semi-polar solvents. There was no significant different on the content of total fibers, with values ranges was from 14.32 g/100 g to 15.39 g/100 g.  However, the highest content of soluble fiber was found in Enhalus acoroides (8.93 g/100 g) and significantly differed to others.